2021
DOI: 10.1038/s41598-021-01707-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the WT2725 dosing emulsion in patients with advanced malignancies

Abstract: WT2725 is a Wilms’ tumor gene 1 (WT1)-derived-oligopeptide vaccine designed to induce WT1-specific cytotoxic T-lymphocytes against WT1+ tumors in human leukocyte antigen (HLA)-A*0201+ and/or HLA-A*0206+ patients. Here, we report the results of a phase I study of WT2725. In this phase I, open-label, dose-escalation and expansion two-part study, the WT2725 dosing emulsion was administered as a monotherapy to patients with advanced malignancies known to overexpress WT1, including glioblastoma. In part 1, 44 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…breast cancer [70] NCT02293707 (phase 2) GX301 four immunogenic peptides from human telomerase and two complementary adjuvants prostate cancer [71] NCT01621542 (phase 1) WT2725 Wilms' tumor gene 1 (WT1)-derived-oligopeptide vaccine glioblastoma [72] NCT03199872 (phase 1/2) RhoC vaccine synthetic long peptide vaccine targeting Ras homolog gene family member C (RhoC)…”
Section: Discussionmentioning
confidence: 99%
“…breast cancer [70] NCT02293707 (phase 2) GX301 four immunogenic peptides from human telomerase and two complementary adjuvants prostate cancer [71] NCT01621542 (phase 1) WT2725 Wilms' tumor gene 1 (WT1)-derived-oligopeptide vaccine glioblastoma [72] NCT03199872 (phase 1/2) RhoC vaccine synthetic long peptide vaccine targeting Ras homolog gene family member C (RhoC)…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated the safety and tolerability of the WT1 peptide-based vaccine in humans, as well as the induction of WT1-specific IgG antibodies [ 26 , 27 , 28 ]. In this context, research is still ongoing [ 29 , 30 ].…”
Section: Vaccine Therapymentioning
confidence: 99%
“…The resulting data demonstrated the induction of WT1-specific IgG antibodies as well as the identification of a potential biomarker [ 35 , 36 ]. This is still an actively researched approach [ 37 , 38 ].…”
Section: Established Immunotherapeutic Approaches: Enhancing T-cell A...mentioning
confidence: 99%